Lenalidomide-induced type II Kounis syndrome: a case report - Hu, Ruihan; He, Guoxiang (Frontiers in Cardiovascular Medicine, 2025)
Kounis syndrome is an allergic myocardial ischemia syndrome triggered by various factors. Herein, we presented a case of a patient with Multiple Myeloma who developed chest pain as a result of lenalidomide use. The patient’s electrocardiogram (ECG) revealed ST-segment depression, along with elevated troponin I and eosinophils levels. Emergency coronary angiography identified thrombosis in the middle segment of the anterior descending branch of the left coronary artery. Previous case reports have linked lenalidomide chemotherapy to myocarditis as the primary form of myocardial damage. This case marks the first documented occurrence of myocardial infarction attributed to lenalidomide, highlighting a previously unrecognized aspect of its cardiotoxic profile.